A disimprisoned epic : form and vision in Carlyle's French Revolution - Cumming, Mark (Anniversary Collection., 1988)
In A Disimprisoned Epic, Mark Cumming elucidates the formal genesis of the French Revolution in Carlyle's literary criticism and reestablishes it as an epic experiment in literary form.